Endothelial progenitor cell-derived microvesicles improve neovascularization in a murine model of hindlimb ischemia - Ranghino, A; Cantaluppi, V; Grange, C; Vitillo, L; Fop, F; Biancone, L; Deregibus, M C; Tetta, C; Segoloni, G P; Camussi, G (International journal of immunopathology and pharmacology, 2012)
Paracrine mediators released from endothelial progenitor cells (EPCs) have been implicated in neoangiogenesis following ischemia. Recently, we demonstrated that microvesicles (MVs) derived from EPCs are able to activate an angiogenic program in quiescent endothelial cells by a horizontal transfer of RNA. In this study we aim to investigate whether EPC-derived MVs are able to induce neoangiogenesis and to enhance recovery in a murine model of hindlimb ischemia. Hindlimb ischemia was induced in severe combined immunodeficient (SCID) mice by ligation and resection of the left femoral artery and mice were treated with EPC-derived MVs (MVs), RNase-inactivated MVs (RnaseMVs), fibroblast-derived MVs or vehicle alone as control (CTL). Since MVs contained the angiogenic miR-126 and miR-296, we evaluated whether microRNAs may account for the angiogenic activities by treating mice with MVs obtained from DICER-knock-down EPC (DICER-MVs). The limb perfusion evaluated by laserdoppler analysis demonstrated that MVs significantly enhanced perfusion in respect to CTL (0.50±0.08 vs 0.39±0.03, p<0.05). After 7 days, immunohistochemical analyses on the gastrocnemius muscle of the ischemic hindlimb showed that MVs but not fibroblast-MVs significantly increased the capillary density in respect to CTL (MVs vs CTL: 24.7±10.3 vs 13.5±6, p<0.0001) and (fibroblast-MVs vs CTL: 10.2±3.4 vs 13.5±6, ns); RNaseMVs and DICER-MVs significantly reduced the effect of MVs (RNaseMVs vs CTL: 15.7±4.1 vs 13.5±6, ns) (MVs vs DICER-MVs 24.7±10.3 vs 18.1±5.8, p <0.05), suggesting a role of RNAs shuttled by MVs. Morphometric analysis confirmed that MVs enhanced limb perfusion and reduced injury. The results of the present study indicate that treatment with EPC-derived MVs improves neovascularization and favors regeneration in severe hindlimb ischemia induced in SCID mice. This suggests a possible use of EPCs-derived MVs for treatment of peripheral arterial disease.